2013
DOI: 10.1055/s-0033-1355394
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Morbidities in Moderate and Late Preterm Infants

Abstract: Nearly half of all infants suffered from any morbidity, and several risk factors were identified being significantly associated with NICU admission rate and length of hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
1
9
0
7
Order By: Relevance
“…In accordance with our results, in a recent study GA at birth was associated with Apgar score at fifth minute for late preterm pregnancies with placenta previa [23]. Indeed, a number of recent studies would advocate the benefits of expectant management, even for late preterm neonates [23] [28] [30] [31]. Nevertheless, after 32th week of gestation the neonatal prognosis is good [32].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance with our results, in a recent study GA at birth was associated with Apgar score at fifth minute for late preterm pregnancies with placenta previa [23]. Indeed, a number of recent studies would advocate the benefits of expectant management, even for late preterm neonates [23] [28] [30] [31]. Nevertheless, after 32th week of gestation the neonatal prognosis is good [32].…”
Section: Discussionsupporting
confidence: 90%
“…However, a series of studies have demonstrated that APH is an independent factor for adverse neonatal outcomes in very preterm, as well as late preterm neonates. Among these groups APH has been independently associated with increased neonatal mortality and morbidity, particularly severe respiratory disorders, increased admission rate to NICU and increased hospital stay [28]- [31]. Our study intended to present an overview of the different causes of APH in the third trimester of pregnancy in relation to the perinatal outcome.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 Therefore, the significant increased risk for preterm births found after in utero exposure to SGAs (OR, 1.85; 95% CI, 1.20-2.86) may pose a significant health care issue. Furthermore, a study by Russell et al 38 (2007) reported that preterm births use significant amounts of health care resources, causing longer hospital stays, and almost 50% of the costs of infant hospitalizations.…”
Section: Discussionmentioning
confidence: 99%
“…Among these groups APH has been independently associated with increased neonatal mortality and morbidity, particularly severe respiratory disorders, increased admission rate to NICU and increased hospital stay. [44][45][46][47] In a study conducted by Johns J et al both preterm delivery and PPROM are related with low birth weight as predictable factors. Our study demonstrated that the fetal weight was lower in the case than control group.…”
Section: Discussionmentioning
confidence: 99%